The Anglo-Scottish Border and the Shaping of Identity, 1300–1600
XII, 235 p. 2 illus.
Keywords: The Anglo-Scottish Border and the Shaping of Identity, 1350-1600 explores the roles that Scotland and England play in one another's imaginations. This collection of essays brings together eminent scholars and emerging voices from the frequently divergent fields of English and Scottish medieval studies.